Post-ISIS Middle East: What is next for the Region? - Mr. Sajid Aziz (CISS Insight Journal, 2017)
In a little over three years after IS/Daesh declared its ‘caliphate’, it has been dislodged from its capital, Mosul. Its fleeing fighters blew up the al-Nuri mosque, where Abu Bakr al-Bagdadi, in an infamous sermon, declared the establishment of ISIS1. Across the border, the United States of America along with the Syrian Democratic Forces (SDF) has been waging a months-long bloody battle against it in Raqqa, its de-facto Syrian capital2. While, Russian and Syrian forces and Shia militias have broken the siege of pro-government areas and the airbase in Deir ez-Zor and driven out ISIS from considerable areas it once controlled3. Prior to this ISIS was defeated in norther Syria by Kurdish forces and in Iraq security forces along with Iranian Revolutionary Guard Corps-trained militias routed ISIS in Fallujah, Tikrit and Ramadi. Both were supported by US Special Forces and aerial strikes. These important security developments have generated plenty of speculations regarding the impending doom of ISIS and as to what a post-ISIS Middle East will look like. This research article is an attempt to assess the evolving security dynamics in Middle East in the backdrop of recent ISIS defeats and the prognostication of its imminent end. It discusses whether the physical dislodgement of ISIS from areas it has controlled for some years predicts its complete annihilation as a terrorist group, as one of the enduring traits of terrorist organizations in recent years has been to revive themselves in different manifestations.